Assessing the evolution of school performance and value-added: trends over four years - M. C. Portela (2013)
This paper explores the changes in value added(VA) of a sample of schools for cohorts of students finishingsecondary education between 2005 and 2008. VAestimates are based on distance measures obtained fromDEA models. These measures are computed for each pupilin each school, and evaluate the distance between theschool frontier in a given year and a pooled frontier comprisingall schools analysed. The school VA is then computedby aggregating the VA scores for the cohort of pupilsattending that school in a given year. The ratio between VAestimates for two consecutive cohorts, that attended theschool in different years, is taken as the index of VAchange. However, the evolution of school performanceover time should consider not only the movements of theschool frontier, but should also take into account othereffects, such as the proximity of the students to the bestpractices,represented by the school frontier, observed overtime. For that purpose we developed an enhanced Malmquistindex to evaluate the evolution of school performanceover time. One of the components of the Malmquist indexproposed measures VA change, and the other measures theability of all school students to move closer to their ownschool best practices over time. The approach developed isapplied to a sample of Portuguese secondary schools.